Employee retention, market orientation, and organizational performance – An empirical study - Fatema Johara; Sofri Yahya; Tehseen, Shehnaz * (International Academic Institute for Science and Technology, Haryana, India, 2018)
Every organization needs to attract, recruit and hold the best talent in today’s competitive environment to survive in the marketplace. The organizations can perform at their best level by utilizing all capabilities of their employees that is possible through employees’ retention. The purpose of this study was to examine the extent to which market orientation assists in achieving organization’s outstanding financial performance by retaining its core employees. A total of 300 self-administrative questionnaires were distributed and only 266 employees gave feedback. Out of 266, response of 18 employees was found incomplete. The data was analyzed with the help of SPSS software. The results demonstrated that market orientation has a significant role in employee retention as well as outstanding organizational financial performance. The outcomes of this study will help organizations understand the importance of market orientation in achieving superior organizational financial performance and in retaining key employees.